Penerapan Model Pembelajaran Snowball Throwing Tema Daerah Tempat Tinggalku Pada Siswa Kelas IV - Lita Aditya Khoirun Nisa’; Wachid Yuli Irfanto (El-Miaz: Jurnal Pemikiran dan Pendidikan Dasar, 2022)
Based on the results of interviews with homeroom teachers, it shows that some of the fourth grade students have not reached the KKM that has been set, which is 70%. So, improvement is needed in the form of applying the innovative snowball throwing learning model. This research was conducted at UPT SD NEGERI 107 GRESIK. This research uses descriptive qualitative research. The research subjects consisted of teachers and students as informants. Data collection techniques used were interviews, questionnaires and documentation. In this study it was found that the teacher had used the learning model very well in the thematic learning process. The teacher has used an interesting model in managing learning, so that learning is conducive and enjoyable. While the results of the questionnaire regarding student responses to learning using the snowball throwing model were very good including perceptions of the use of learning models by students, student responses to the use of learning models, the frequency of using learning models by teachers. Based on the results of the research that has been done, the general conclusions obtained regarding the application of the snowball throwing learning model to the learning outcomes of fourth grade elementary school students are very good.